Development of reading skills through phonemic awareness in 5th grade EFL students in Daule. - Espinel Alvarado, Fernando Nahin (2025)
Phonemic awareness is crucial in reading instruction because it allows students to recognize and manipulate sounds, facilitating word decoding and text comprehension. This research focused on evaluating the development of phonemic awareness to improve the reading skills of 5th-grade EFL students at the Unidad Educativa Bilingüe Torremar. A descriptive methodology was used with a mixed approach (quantitative and qualitative) through a test for the students and an in-depth interview with the teacher. The participants who made up this research were ten male students from level A with an A2 English proficiency level. The main findings obtained were that students demonstrated a moderate level of phonemic awareness with a score ranging from 5.5 to 10, the development of phonemic awareness directly affects students' reading skills, and teaching strategies to improve reading skills through phonemic awareness include reading aloud, use of audio materials, among others.